Inconsistency in Political Bride Price (Mahar) Criminal Arrangements in Presidential Elections - Zubairi, Zubairi (Law Research Review Quarterly, 2018)
Setting the threshold of the nomination of the President in Article 222 of Law Number 7 of 2017 makes political parties election participants who do not meet must join with other political parties. This has the potential to lead to political dowry actions because a combination of political parties can only carry one pair of candidates for President and Vice President. Mahar politics have actually been banned in Article 228 of the Election Law, but they are not equipped with clear sanctions. This type of research is legal research. The Election Law does not regulate criminal sanctions against political dowry measures. The only sanctions that can be imposed are only administrative witnesses in the form of a ban on nominating candidates in the next period. Unfortunately the sanctions only apply to political party recipients of political dowry (Article 228 paragraph [2] and [4] of the Election Law). Though in principle the political dowry is certainly a crime so there must be criminal sanctions. This is certainly different from the provisions in Article 47 juncto Article 187B-187C Law Number 10 Year 2016 (UU Pilkada), which regulates dowry actions in the process of nominating a regional head qualified as a criminal offense in which the giver and the recipient are threatened with criminal sanctions in the form of criminal prison and fines. There are different arrangements in the Election Law and the Election Law. The Election Law does not regulate criminal dowry politics, whereas the Election Law regulates it.